REPRESENTATION OF THE EMOTIONAL STATE «FEAR» IN TATAR PHRASEOLOGY - Leysan Ildusovna Ismagilova (Sovremennye Issledovaniâ Socialʹnyh Problem, 2020)
The purpose of this paper is to analyse phraseological units of the Tatar language that reflect the emotional state of fear; to study semantic and anthropocentric organization of phraseological units. The object of the analysis is phraseological units of the Tatar language reflecting the state of «fear».